Suitabilityof Different Winter Vegetables with Sweet Gourd (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at Joydebpur and Rajbari Farm of Bangladesh Agricultural Research Institute during two successive rabi seasons (2014-16) to find out the suitable vegetable for intercropping with sweet gourd for higher productivity and economic return. Six intercrop combinations of sweet gourd and vegetables viz., T1 = Sole sweet gourd, T2  = Sweet gourd (2 m x 2 m) + cabbage (50 cm x 50 cm), T3 = Sweet gourd (2m x 2m) + cauliflower (50 cm x 50 cm), T4 = Sweet gourd (2 m x 2 m) + radish (20 cm x 25 cm), T5 = Sweet gourd (2 m x 2 m) + lettuce (50 cm x 50 cm), T6 = Sweet gourd (2 m x 2 m) + tomato (50 cm x 50 cm) were tested  at Joydebpur  and Rajbari. The highest mean sweet gourd yield (31.37 t ha-1 at Joydebpur and 34.54 t ha-1 at Rajbari) was recorded in sole sweet gourd over the years. The highest mean vegetable yield (42.87 t   ha-1 at Joydebpur and 61.40 t ha-1 at Rajbari) was recorded in sweet gourd + cabbage combination. Maximum mean sweet gourd equivalent (SEY) yield (72.55 t ha-1), highest gross return (Tk. 362775 ha-1 and BCR (2.98) were recorded in sweet gourd + cabbage combination over the years at Joydebpur. The maximum mean SEY (79.38 t ha-1), highest gross return (Tk. 396905 ha-1) and BCR (3.25) were recorded in sweet gourd + cauliflower combination at Rajbari. Two year results revealed that sweet gourd + cabbage and cauliflower might be suitable intercrop combination for getting maximum yield and economic returnBangladesh Agron. J. 2018, 21(2): 7-11